ANALISIS KEANDALAN SISTEM PADA LAYANAN DRIVE THROUGH DAN COUNTER SERVICE - Mar’atus Sholihah (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2018)
This study aims to analyze the relationship between drive through service and counter service in KFC Manahan by using reliability theory. In this study it can be seen which service is superior and what configuration can be applied. This study also attempts to test the researcher’s findings about reliability configuration with what KFC Manahan claims to.This research is a research with primary data source. The data in this research is obtained by observation and direct interview in KFC Manahan for 2 weeks long, in June 2018. To analyze the data, this study used reliability concept with excel solver.The result of this research is that the Counter Service (89%) has the higher score than the Drive Through (21%) Service. The results also show the relevance with the claims of KFC Manahan, and the Parallel Configuration is used. Keywords: Drive Through, Counter Service, Configuration, Reliability